Consistent context aware behaviour in smart home environment. (3rd April 2019) - Subbaraj, Rajarajeswari; Venkatraman, Neelanarayanan
The home automation controls the electronic devices remotely and automatically with the help of context aware behaviour. Context awareness is the process where data from various sensors and input from user or user action must be interpreted and corresponding commands to actuators must be generated. This context aware automation and decision support process is done with the help of adaptive rules which is defined for the automatic behaviour of devices in the smart home environment. The consistent behaviour of the devices in the smart environment will capture the customer satisfaction. This work describes the process of checking the consistent behaviour of the context aware system in smart home environment using formal modelling and verification method. We have discussed a mechanism to check the consistent behaviour of the adaptive mechanism of smart home environment. The result ensures the consistent behaviour of the context aware system in the smart environment.